Trade‐Off between Trap Filling, Trap Creation, and Charge Recombination Results in Performance Increase at Ultralow Doping Levels in Bulk Heterojunction Solar Cells. Issue 24 (23rd August 2016) - Shang, Zhengrong; Heumueller, Thomas; Prasanna, Rohit; Burkhard, George F.; Naab, Benjamin D.; Bao, Zhenan; McGehee, Michael D.; Salleo, Alberto
Abstract : Doping of organic bulk heterojunction solar cells has the potential to improve their power conversion efficiency (PCE). Deconvoluting the effect of doping on charge transport, recombination, and energetic disorder remains challenging. It is demonstrated that molecular doping has two competing effects: on one hand, dopant ions create additional traps while on the other hand free dopant‐induced charges fill deep states possibly leading to V OC and mobility increases. It is shown that molar dopant concentrations as low as a few parts per million can improve the PCE of organic bulk heterojunctions. Higher concentrations degrade the performance of the cells. In doped cells where PCE is observed to increase, such improvement cannot be attributed to better charge transport. Instead, the V OC increase in unannealed P3HT:PCBM cells upon doping is indeed due to trap filling, while for annealed P3HT:PCBM cells the change in V OC is related to morphology changes and dopant segregation. In PCDTBT:PC70BM cells, the enhanced PCE upon doping is explained by changes in the thickness of the active layer. This study highlights the complexity of bulk doping in organic solar cells due to the generally low doping efficiency and the constraint on doping concentrations to avoid carrier recombination and adverse morphology changes. Abstract : Ultralow level doping (≈ppm) can increase the power conversion efficiency of organic solar cells . Trap states filling by free charges and trap creation by dopant ions have competing effects on carrier mobility and open circuit voltage thereby imposing constraints on the effectiveness of doping. Measurements are performed to study what electronic process dominates in different materials or fabrication conditions.